ESG quality as a factor for resilience in crises. Critical analysis of the impact of ESG ratings on capital market performance of German companies in volatile markets - Bloch, Jonas Simon (2024)
In recent years companies have faced extensive challenges with crises like Covid-19 and the Russian invasion of Ukraine, resulting in risks for investors. Simultaneously, the concept of ESG gained importance. However, research about the ESG concept can be used to mitigate these risks is limited. Therefore, this thesis aims to provide a contribution to the research on how ESG quality can affect the resilience in crises. A sample of 40 major German companies was analyzed on how their ESG ratings affects their capital market performance. A cross-sectional regression model was used to evaluate a potential causal relationship between the ESG score and volatility, return and Sharpe ratio for periods with exceptionally high volatility from 2019 to 2023. Even though a statistically significant causal relationship could not be proven, strong indicators for correlation exist.